Effective Marketing Strategy in Facing Tight Competition - Suharto, Suharto (Journal Arbitrase : Economy, Management and Accounting, 2023)
Increasingly fierce competition requires a planned and adaptive marketing approach to maintain and increase market share. This research aims to identify and analyze effective marketing strategies for companies in facing intense competition in the market. This research uses a qualitative approach with descriptive methods. The results of this research conclude that an effective marketing strategy in facing intense competition involves recognizing competitors, understanding the target market, continuous innovation, building a strong brand image, expanding market reach, collaborating with business partners, and superior customer service. Through this holistic approach, companies can build a solid foundation to survive and grow in a competitive market. Implementing this strategy provides opportunities to increase market share, increase customer loyalty, and create sustainable competitive advantages in an ever-changing business era.